An outbreak of Vibrio alginolyticus infection in juvenile sea cucumbers Holothuria scabra in Sabah, Malaysia - Othman, Rafidah; Nawi, Mohd Firdaus; Muhamad Shaleh, Sitti Raehanah; Md Yasin, Ina Salwany; Ching, Fui Fui; Abidin, N. A.; Saad, Mohd Zamri (Universiti Putra Malaysia Press, 2017)
Sea cucumber breeding was carried out in Universiti Malaysia Sabah Hatchery Facilities in April 2015. Approximately 690,000 eggs were fertilised with a hatching rate of 9%, an estimated 60,000 larvae were produced. In June, the surviving 359 sea cucumber juveniles were sorted according to size. In late July, it was found that only 30 juvenile sea cucumbers had survived, and the remaining were dead, with multiple ulcers on the skin and excessive mucus covering the entire body. In December 2015, a total of 20 juvenile sea cucumbers were sampled for bacterial isolation and histopathological examinations. Vibrio alginolyticus was isolated and histopathological examinations revealed peracute inflammation and accumulation of extensive mucus surrounding the body.